Localization of Minodronate in Mouse Femora Through Isotope Microscopy. (October 2016) - Hongo, Hiromi; Sasaki, Muneteru; Kobayashi, Sachio; Hasegawa, Tomoka; Yamamoto, Tomomaya; Tsuboi, Kanako; Tsuchiya, Erika; Nagai, Tomoya; Khadiza, Naznin; Abe, Miki; Kudo, Ai; Oda, Kimimitsu; et al.
Minodronate is highlighted for its marked and sustained effects on osteoporotic bones. To determine the duration of minodronate's effects, we have assessed the localization of the drug in mouse bones through isotope microscopy, after labeling it with a stable nitrogen isotope ([ 15 N]-minodronate). In addition, minodronate-treated bones were assessed by histochemistry and transmission electron microscopy (TEM). Eight-week-old male ICR mice received [ 15 N]-minodronate (1 mg/kg) intravenously and were sacrificed after 3 hr, 24 hr, 1 week, and 1 month. Isotope microscopy showed that [ 15 N]-minodronate was present mainly beneath osteoblasts rather than nearby osteoclasts. At 3 hr after minodronate administration, histochemistry and TEM showed osteoclasts with well-developed ruffled borders. However, osteoclasts were roughly attached to the bone surfaces and did not feature ruffled borders at 24 hr after minodronate administration. The numbers of tartrate-resistant acid phosphatase–positive osteoclasts and alkaline phosphatase–reactive osteoblastic area were not reduced suddenly, and apoptotic osteoclasts appeared in 1 week and 1 month after the injections. Von Kossa staining demonstrated that osteoclasts treated with minodronate did not incorporate mineralized bone matrix. Taken together, minodronate accumulates in bone underneath osteoblasts rather than under bone-resorbing osteoclasts; therefore, it is likely that the minodronate-coated bone matrix is resistant to osteoclastic resorption, which results in a long-lasting and bone-preserving effect.